Optimal forage and supplement balance for organic dairy farms in the Southeastern United States. (April 2021) - Allison, John; Burdine, Kenneth H.; Dillon, Carl; Smith, S. Ray; Butler, David M.; Bates, Gary E.; Pighetti, Gina M.
Abstract: Context: With prevailing economic concerns facing the conventional dairy industry, organic production is a potential alternative for dairy producers as evidenced by a substantial number of operations pursuing organic markets in an effort to improve profitability. However, economic research is limited and the long-term economic sustainability of the system has been questioned. Objective: The objectives of this study were to determine the economically optimal mix of forage and supplemental feed to maximize net returns, identify opportunities and considerations regarding production and feed management, and determine the sensitivity of returns relative to changes in milk prices for an organic dairy operation. Methods: A linear programming model was developed to represent a whole-farm organic dairy operation in the Southeastern United States. The representative farm modeled was based on actual organic dairy operations in Kentucky and Tennessee, partnering with University personnel on this project. The model was employed to explore and optimize enterprise and feed options for the operation. Results and conclusions: Results demonstrated a degree of substitutability of ration components, including representative forage species mixes for grazing, as well as hay and purchased concentrates. Profit potential was found to exist at assumed organic milk price levels, although organic milk price trends and the cost of transitioning to organic production create significant challenges. While a considerable reliance on grazing was a cost-effective feeding decision for organic production (a minimum of 30% dry matter intake from grazing is required), increased milk volumes justified the production and purchasing of additional supplemental feeds. Thus, evidence of increased profit potential by targeting higher production levels was suggested under the scenarios examined. Results also indicated a relatively narrow range of break-even milk prices across varying production levels for organic dairies. Finally, a business life of twenty years was generally needed to justify the transitioning of an existing conventional dairy to an organic dairy operation. Significance: This work has implications for existing dairy operations as findings suggest profit potential and some ability to withstand moderate erosion of milk price. The work also informs dairy producers interested in transitioning to organic production by quantifying the cost of this transition and the potential return on that investment over time. Graphical abstract: Unlabelled Image Highlights: A whole farm model was used to determine profit maximizing production level and feeding program for an organic dairy. Profit potential was found for existing organic dairies with some ability to withstand moderate decreases in milk price. Returns increased as production level rose, even though dependence on purchased feed increased. Profitable transition of a traditional dairy to organic production generally required an expected 20 year business life.